Determination of indium by adsorptive stripping voltammetry at the bismuth film electrode using combined electrode system facilitating medium exchange - Martynov, Leonid Yu, (2024)
A novel method of determining indium has been described in this article which uses adsorptive stripping voltammetry (AdSV) and 4-(2-pyridylazo)-resorcinol (PAR) as a chelating agent or as the preconcentration agent. The measurements were performed using square-wave voltammetry by using a combined electrode system, which allows for preconcentration and stripping without opening the circuit. Ex situ plated bismuth film electrode (BiFE) was used as the working electrode. A potential-time program was developed for the inversion cycle stages based on the various factors that affect the magnitude of the inversion signal. The calibration curve was linear in a concentration range of 2·10-7 to 4·10-6 М when the pH is 4.8, accumulation potential is -700 mV, and PAR concentration is 1·10-4 M. The detection limit for the 3σ criterion with an accumulation time of 120 s was 3.5·10-9 М. Several interferences caused by Tl(I), Zn(II), Cu(II), Pb(II), Co(II), Ni(II), Mn(II), Fe(III), Cr(III) ions have been studied, and it has been shown that medium exchange procedure can effectively eliminate some interferences. It was demonstrated that the method can be applied to the determination of indium in tap water and in ITO glass sample.